Tathbiq Thariqah Al-Tikrar Fi Tahsin Al-Ada’ Al-Shauti li Al-Athfal fi Raudhah Al-Qur’an “Nur Al-Haq” Labung - Junia Safreni (Rumah Jurnal IAIN Bukittinggi, 2021)
This research aims to answer the question is whether the method of repetition in improving the vocal performance of the children of the Qur'an Kindergarten